Formulasi Sinbiotik Terenkapsulasi Berbasis Fitase untuk Meningkatkan Kadar Fosfor Pakan Unggas - Ihza Agistna; Khairil Anwar; Muhamad Ali; Djoko Kisworo; Anwar Rosyidi; Budi Indarsih; Zaid Al Gifari (Politeknik Pembangunan Pertanian Malang, 2025)
This study aimed to optimize the utilization of rice bran as poultry feed through the development of a synbiotic containing lactic acid bacteria (Pediococcus pentosaceus) capable of producing the enzyme phytase. Although rice bran contains a high amount of phosphorus, most of it is bound in the form of phytic acid, which is poorly digested by poultry. Therefore, the ability of P. pentosaceus to hydrolyze phytate in rice bran was evaluated through a fermentation process, indicated by an increase in free phosphorus levels. Subsequently, the synbiotic formulation was encapsulated using the extrusion method with natural coating materials, sodium alginate and chitosan. In-vitro viability tests were conducted under simulated gastrointestinal conditions at pH 2.0 and 7.2, with incubation times of 1 to 3 hours at 37°C, and varying chitosan concentrations of 1%, 2%, and 3%. The results showed that P. pentosaceus effectively hydrolyzed phytic acid, as indicated by an 18% increase in phosphorus after 72 hours of incubation. Moreover, encapsulation using 3% chitosan was the most effective in maintaining bacterial viability, reaching 25.33 log CFU/ml at pH 7.2 and 22.00 log CFU/ml at pH 2.0. This study concludes that encapsulated synbiotics have the potential to serve as functional feed to improve the efficiency of rice bran utilization in poultry.